Traditional Figures Marketing Communication Activation on Is Yuniarto's Digital Wayang Design: - - Dewi Sad Tanti; Hidayatullah, Wiyanto; Bagus Pragnya (LPPM Stikosa - AWS, 2023)
Is Yuniarto is a comic artist and art illustrator who uses digital platform for sharing his digital comics or designs into the digital world. His works can be seen on Instagram @is.yuniarto where he redesigns fictional hero characters from abroad by adding a traditional Indonesian touch and making the results even better. This study aims to find Discourse of Traditional Figure Marketing Communication Activation on Is Yuniarto’s Digital Wayang Designs. The type of research used is descriptive research with a qualitative approach. The method used is semiotics. The result is the theme of wayang design by Is Yuniarto is 'Adiwira Kalangga VS para Adidurja’. Adiwira Kalangga is Hero form Country Kalangga. Kalangga is like Trowulan by making a local name that is similar to Marvel serial characters universally. Figure seven Adidurja is powerful and intelligent supernatural.The characters depicted by isyuniarto actually want to match the characters in the Marvel series and then use local terms as a form of character similarity. Figures that are marketed include, among others, Kalangga, Kalawisa, Kalagetih, Biawak, Khageswara, Ki Astapadha, Bajra and Tuyul ijo. The depiction of figures through character traits, supernatural powers, colors, and weapons ownership. Is Yuniarto branding new figure of wayang design. His digital content communication competence in design is uniqueness.Philosophy in design activation its his strength.